Repurchase intent antecedents of a competitive brand in the smartphones segment. Issue 5 (4th July 2019) - Sperandio Milan, Gabriel; Zanchet de Lima, Vinicius; Eberle, Luciene; De Toni, Deonir; Bebber, Suélen
Abstract: This research has analyzed the influence of perceived value, affective commitment, normative commitment and positive word of mouth as antecedents of repurchase intention of smartphones of a particular brand. The analysis of the results was made by means of multivariate statistics, applying Structural Equation Modeling technique. The sample consisted of 283 valid cases. The results showed that perceived value positively influences the affective commitment and normative commitment; perceived value by customers does not positively influences positive word of mouth; affective commitment positively influences positive word of mouth; affective commitment positively influences repurchase intention; normative commitment positively influences repurchase intention; and positive word of mouth positively influences repurchase intention of a product of the same brand.